The Effect of Sitting Motion Exercise and Plank on Back Style Swimming Skills of Students Faculty of Sports Science Universitas Jambi - Ilham Ilham; Sabaruddin Yunis Bangun (Universitas Negeri Medan, 2021)
This study examines the effect of sitting and plank exercises on the backstroke swimming skills of students of the Faculty of Sports Science, Jambi University, in the second semester of the Sports Coaching Study Program. The benefits of this research include: (1) For swimming coaches, it can be used as a basis for training athletes to improve backstroke swimming skills. (2) Lecturers who teach swimming courses and teachers are meant to be used as a reference in teaching their students or students in improving their backstroke swimming skills. (3) For academics or scientists, the results of this research can be used as reference material and add scientific insight, especially those who study backstroke swimming. (4) For athletes in the backstroke, it is for them to do motion exercises while sitting and plank to improve the arm muscles, abdominal muscles, and leg muscles themselves to improve their backstroke swimming skills and speed. This research is an experimental study that uses the One Group Pretest-Postest Design, where the independent variable is exercise while sitting and plank. In contrast, the dependent variable is the backstroke swimming skill. The research instrument is the backstroke swimming skill test, using an observation sheet to observe the backstroke swimming skills carried out by the sample by matching the observation sheet tested for validity and reliability. The data collected were analyzed using the t test, which was previously carried out by the normality test. Based on the results of hypothesis testing, it was obtained Ttable > Ttable (36.360 > 1.66). The results of this hypothesis test indicate an effect of sitting motion exercises and planks on the backstroke swimming skills of students of the Faculty of Sports Science, Jambi University, in the second semester of the Sports Coaching Study Program.